Amorphous MoS3 Infiltrated with Carbon Nanotubes as an Advanced Anode Material of Sodium‐Ion Batteries with Large Gravimetric, Areal, and Volumetric Capacities. Issue 5 (17th November 2016) - Ye, Hualin; Wang, Lu; Deng, Shuo; Zeng, Xiaoqiao; Nie, Kaiqi; Duchesne, Paul N.; Wang, Bo; Liu, Simon; Zhou, Junhua; Zhao, Feipeng; Han, Na; Zhang, Peng; et al.
Abstract : The search for earth‐abundant and high‐performance electrode materials for sodium‐ion batteries represents an important challenge to current battery research. 2D transition metal dichalcogenides, particularly MoS2, have attracted increasing attention recently, but few of them so far have been able to meet expectations. In this study, it is demonstrated that another phase of molybdenum sulfide—amorphous chain‐like MoS3 —can be a better choice as the anode material of sodium‐ion batteries. Highly compact MoS3 particles infiltrated with carbon nanotubes are prepared via the facile acid precipitation method in ethylene glycol. Compared to crystalline MoS2, the resultant amorphous MoS3 not only exhibits impressive gravimetric performance—featuring excellent specific capacity (≈615 mA h g −1 ), rate capability (235 mA h g −1 at 20 A g −1 ), and cycling stability but also shows exceptional volumetric capacity of ≈1000 mA h cm −3 and an areal capacity of >6.0 mA h cm −2 at very high areal loadings of active materials (up to 12 mg cm −2 ). The experimental results are supported by density functional theory simulations showing that the 1D chains of MoS3 can facilitate the adsorption and diffusion of Na + ions. At last, it is demonstrated that the MoS3 anode can be paired with an Na3 V2 (PO4 )3 cathode to afford full cells with great capacity and cycling performance. Abstract : The preparation of compact MoS3 particles via the facile acid precipitation method leads to a high‐performance sodium‐ion battery anode material. Contrary to the well‐studied layered MoS2, amorphous MoS3 consists of Mo chains bridged by sulfide and disulfide ligands. It demonstrates improved electrochemical performance with large specific capacity, excellent rate capability and satisfactory cycling stability.